Pengujian Black Box pada Aplikasi Penjualan Berbasis Web Menggunakan Teknik Boundary Value Analysis - Nurudin, Muhamad; Jayanti, Windi; Saputro, Rio Dwi; Saputra, Masda Priadyan; Yulianti, Yulianti (Jurnal Informatika Universitas Pamulang, 2019)
In a software test, validation is one of the processes of checking whether the software meets the expected specifications and objectives or not. The data validation process has not been maximized can result in a mismatch of data that will be stored in the database. For example the amount of stock turned negative, or the number of digits entered can exceed the defined limits. This can be detrimental to the owner and user in using this application. Therefore, it is necessary to improve the quality of validation more accurately, so it can help the owner in terms of data accuracy. Applications are designed in such a way must go through a testing phase to ensure the quality of the software itself. Examples of tests can be said to be good if they have a chance of finding an error that cannot be revealed. Among the many ways of the Black Box testing methods, this study uses the Boundary Value Analysis testing method. The method tests the maximum number of limits and the minimum number of limits to produce a valid value, which is considered quite relevant for testing sales applications at PT Karunia Segar Kedua. The initial stage of the research needs to be done is to define the functionality to be tested, compile the test scheme, choose the material to be tested, determine the maximum and minimum number of limits in accordance with a predetermined database structure, conduct experiments, document research results, and draw conclusions. The conclusion is based on the testing has been done is software can be used properly, after an improvement is made on the errors found. However, this test has not been said to be perfect, because it is only done using a sample form. From the results of this test it is expected that the application can be used according to user requirements.